2022
DOI: 10.1016/j.lrr.2021.100286
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Myeloid Sarcoma with TP53 mutated Myelodysplastic Syndrome/Myeloproliferative Neoplasm Overlap syndrome: Response to Decitabine-Venetoclax regimen

Abstract: Myeloid sarcoma (MS) is a rare extramedullary blast proliferation of immature cells of myeloid origin. It is commonly associated with acute myeloid leukemia (AML), myelodysplastic syndrome (MDS), or myeloproliferative neoplasm (MPN), and may precede, coincide with, or follow the diagnosis of a myeloid disorder. MS treatment is controversial, but AML induction like regimens is usually recommended. We present an unusual case of de novo TP53 mutated MDS/MPN overlap with bladder MS. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It has also been reported that a patient with bladder MS with TP53 mutation achieved a significant improvement in symptoms and achieved complete CR in the first cycle of 20 mg decitabine treatment combined with induction chemotherapy. Due to the consideration of high-risk cytogenetics and TP53 mutations, subsequent allo-HCT was performed for consolidation ( 4 ). Similarly, the patient reported in the present study was treated with decitabine combined chemotherapy and achieved CR after the first chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has also been reported that a patient with bladder MS with TP53 mutation achieved a significant improvement in symptoms and achieved complete CR in the first cycle of 20 mg decitabine treatment combined with induction chemotherapy. Due to the consideration of high-risk cytogenetics and TP53 mutations, subsequent allo-HCT was performed for consolidation ( 4 ). Similarly, the patient reported in the present study was treated with decitabine combined chemotherapy and achieved CR after the first chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Decitabine is often used to treat elderly patients with AML or patients with high-risk chemoresistant phenotypes (23). Some studies have confirmed the efficacy of decitabine in the treatment of MS, reporting that it can induce long-term remission (4,24). In a Surveillance, Epidemiology and End Results database analysis, Liang et al (13) found that when using overall survival as an indicator of efficacy, patients with non-isolated MS showed an improved response to cytarabine-based AML chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations